Microparticle impact-bonding modes for mismatched metals: From co-deformation to splatting and penetration. (15th October 2020) - Hassani, Mostafa; Veysset, David; Sun, Yuchen; Nelson, Keith A.; Schuh, Christopher A.
Abstract: We present a comprehensive experimental campaign of high-velocity microparticle impacts with different combinations of particle and substrate materials to identify possible deformation regimes. Based on experimental observations of the impact sites, we identify three typical modes of behavior, namely, splatting, co-deformation, and penetration. We develop a theoretical framework to predict the operative regime for a given particle/substrate combination, ranging from splatting and penetration at two extremes of a spectrum, and co-deformation in the center. We propose an impact ratio based on the materials' properties, which can successfully quantify the spectrum. Co-deformation is expected when the ratio is around unity, while much larger or smaller ratios give rise to penetration and splatting, respectively. Graphical abstract: Image, graphical abstract